2022
DOI: 10.1186/s41927-022-00312-9
|View full text |Cite
|
Sign up to set email alerts
|

The importance of children and young person involvement in scoping the need for a paediatric glucocorticoid-associated patient reported outcome measure

Abstract: Background For many children and young people (CYP) with paediatric rheumatic conditions, glucocorticoid medications and their associated side-effects have a substantial impact on disease experience. Whilst there are physician-rated measures of glucocorticoid toxicity, no parallel patient reported measure has been developed to date for CYP with rheumatic disease. This manuscript describes a series of public patient involvement (PPI) events to inform the development of a future paediatric glucoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Marinello et al [ 2 ] incorporated PPI into their practice via a new BehçeTalk Programme, empowering rare disease patients through education and capacity building to promote active involvement in therapeutic decision-making. Singhal et al and Elliott et al focused on engaging young people in research to improve patient-reported outcome measures and communication [ 3 , 4 ]. Esen et al [ 5 ] went one step further, sharing the voices of young people in rheumatology research via the development of an enduring national youth advisory group that is active and eager to co-create throughout all stages of the research cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Marinello et al [ 2 ] incorporated PPI into their practice via a new BehçeTalk Programme, empowering rare disease patients through education and capacity building to promote active involvement in therapeutic decision-making. Singhal et al and Elliott et al focused on engaging young people in research to improve patient-reported outcome measures and communication [ 3 , 4 ]. Esen et al [ 5 ] went one step further, sharing the voices of young people in rheumatology research via the development of an enduring national youth advisory group that is active and eager to co-create throughout all stages of the research cycle.…”
Section: Introductionmentioning
confidence: 99%